The Impact of Customer Treatment on the Resiliency of Selected Food Delivery Riders at Grab Company: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Grab Food now has the widest restaurant selection in the Philippines, with 4,000 locally-based restaurants onboard. Grab Food continues to satisfy more cravings as it bringsgreater convenience to its consumers. We know Filipino consumers love a variety of foodchoices, so we’ve worked hard over the past months to bring onboard their local favoritemerchants onto Grab Food. Today, we have the widest selection of restaurants on GrabFood. Food remains a top household expenditure in the Philippines, and we believe our on-demand food delivery service can add convenience to consumers’ lives while opening upmore income streams for the merchant- and delivery partners. Grab keeps empowering itsintricate network of customers, merchants, and delivery companies. Grab Food is improvinghow well it can make use of shared digital economy prospects.The results of this study reveal that the profile of the respondents in terms of age, sex, andlength of service and also the customer treatment that affects the resiliency of food deliveryriders was evaluated as "strongly agree" in terms of job performance, and job satisfaction,while behavior was evaluated as "agree; The problems encountered in terms of mistakes inorder had the highest rank.This chapter includes a summary of the findings gathered from the study and what the studysuggested. This includes the totality of outcomes of the conducted and the conclusions, andthis study recommends that a way to increase the resiliency of food delivery riders is toimprove their handling of customer orders because it is within the rules of the company totake care of the customer's orders. Doing so can increase the probability of obtaining a goodrating from the customers and also improve proper food handling because proper foodhandling may encourage riders to be more careful and mindful of how they handle food.
Keywords: Business Administration